Collaborative R&D and the national research joint venture database : a statistical analysis - Link, Albert N. (Bingley, U.K. : Emerald Publishing Limited, 2021)
In light of a history of legislative actions in the United States to encourage collaborative R&D, this book characterizes U.S. collaborative R&D through the eyes of the National Research Joint Venture Database. Facilitating a fresh statistical look at collaborative R&D as a purposive strategy in the light of existing public policies, this book also provides a critical evaluation of the effectiveness of those attendant policies. Through an original project-based micro database, the author reveals the patterns of competitive behavior associated with collaborative R&D. Accompanied by follow-up statistical and econometric analyses, readers are not only confronted with what might be the most complete picture of U.S. collaborative R&D to date, but they are also provided with key indications of the effectiveness of U.S. legislative actions which is set to inspire further collaborations in research.
Chapter 1. Introduction. -- Chapter 2. Research joint ventures: theory and evidence -- Chapter 3. National research joint venture database -- Chapter 4. An assessment of the National Cooperative Research Act -- Chapter 5. Characteristics of RJVs -- Chapter 6. Research patterns among RJVs -- Chapter 7. Was the National Cooperative Research Act of 1984 successful? -- Chapter 8. Concluding remarks.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Research, Industrial -- United States; Business & Economics -- Research & Development; Research & development management